2013
DOI: 10.1002/latj.201390036
|View full text |Cite
|
Sign up to set email alerts
|

High‐power Full Penetration Welding Behavior

Abstract: AuTHORSDue to their different physical beam characteristics, there are fundamental differences in the process behavior of Co 2 lasers and solid-state lasers during deep penetration welding. High-quality full penetration welds can be achieved in thick sheet metal with both beam sources. However, the beam sources differ in regards to productivity, process stability, and seam quality depending on the material being welded.CO 2 lasers and solid-state lasers (SSLs) are the most commonly used beam sources for laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…At larger defocusing distances (FPP > 30 mm), the humping and then the lack of penetration (at FPP ≈ 40 mm) occur due to larger spot diameter at the surface, and thus lower power intensity. This trend agrees with other researchers [6,18,27]. There is a possible process window, characterized by a smooth root appearance with a slight reinforcement, when there is a balance between laser power and FPP to obtain full penetration and the occurrence of melt ejections.…”
Section: Welds With 20°bevelling Anglesupporting
confidence: 92%
See 2 more Smart Citations
“…At larger defocusing distances (FPP > 30 mm), the humping and then the lack of penetration (at FPP ≈ 40 mm) occur due to larger spot diameter at the surface, and thus lower power intensity. This trend agrees with other researchers [6,18,27]. There is a possible process window, characterized by a smooth root appearance with a slight reinforcement, when there is a balance between laser power and FPP to obtain full penetration and the occurrence of melt ejections.…”
Section: Welds With 20°bevelling Anglesupporting
confidence: 92%
“…3.8), a Fig. 15 Comparison of present study case a with published results from b, c TRUMPF GmbH [5,27] and d, e Osaka University [18]. IP is incomplete penetration, H is humping mode, GR is bandwidth providing good (acceptable) root quality, and ME is melt ejection mode.…”
Section: Microstructure and Hardnessmentioning
confidence: 66%
See 1 more Smart Citation
“…Evidently, with an increase of plate thickness from 12 to 15 mm, the frequency of humping occurrence is higher due to an increased molten mass of the weld pool. It was shown that duplex stainless steels having very different chemical composition provides much less humping [55]. Pan et al [56] showed that the use of CO 2 in the shielding gas significantly increased the process window, which may be attributed to the change of molten metal chemistry and physical properties such as surface tension.…”
Section: Humping Mechanismmentioning
confidence: 99%